Aggressive Behavior in Broken Home Teens: Can Authoritarian Parenting and Self-Control Have an Impact? - Yandita, Fierro Meioris; Putrie Dimala, Cempaka; Pertiwi, Anggun (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Adolescents from broken homes tend to experience disturbances in emotional and social development due to a lack of attachment and support from parents. Disharmonious family conditions can lead to psychological stress that leads to aggressive behavior. This study aims to examine the influence of authoritarian parenting and self-control on aggressive behavior in adolescents from broken homes in Karawang Regency. This study used a quantitative approach with a causality design. The population in this study were adolescents aged 12–18 years in Karawang Regency with a total of ± 400,000. The sampling method used was non-probability sampling with convenience sampling technique. The determination of the number of samples used the Isaac and Michael formula with a 5% error rate, requiring a minimum of 348 participants. To measure authoritarian parenting, the Parenting Styles and Dimensions Questionnaire (PSDQ) scale from Robinson was used. Self-control was measured using the Brief Self-Control Scale (BSCS) from Tangney, and aggressive behavior was measured using the Aggression Questionnaire developed by Buss and Perry. The analysis results show a significance value of 0.000 < 0.05, meaning there is a significant influence between authoritarian parenting and self-control on aggressive behavior. The results of the determination coefficient test (R Square) show a figure of 0.708 or 70.8%. Authoritarian parenting has a greater influence of 48%, while self-control is 22.8%. The implications of this study indicate that parents and caregivers need to avoid authoritarian parenting that can trigger aggressive behavior in adolescents, as well as the importance of strengthening self-control through emotional education, counseling guidance, and positive activities in the family and school environment to form more adaptive behavior.